Unbalancing Zur (FurB)‐mediated homeostasis in Anabaena sp. PCC7120: Consequences on metal trafficking, heterocyst development and biofilm formation - Irene Olivan‐Muro; Cristina Sarasa‐Buisan; Jorge Guio; Jesús Arenas; Emma Sevilla; Maria F. Fillat (Environmental Microbiology, 2023)
Zinc is required for the activity of many enzymes and plays an essential role in gene regulation and redox homeostasis. In Anabaena ( Nostoc ) sp. PCC7120, the genes involved in zinc uptake and transport are controlled by the metalloregulator Zur (FurB). Comparative transcriptomics of a zur mutant (Δ zur ) with the parent strain unveiled unexpected links between zinc homeostasis and other metabolic pathways. A notable increase in the transcription of numerous desiccation tolerance‐related genes, including genes involved in the synthesis of trehalose and the transference of saccharide moieties, among many others, was detected. Biofilm formation analysis under static conditions revealed a reduced capacity of Δ zur filaments to form biofilms compared to the parent strain, and such capacity was enhanced when Zur was overexpressed. Furthermore, microscopy analysis revealed that zur expression is required for the correct formation of the envelope polysaccharide layer in the heterocyst, as Δ zur cells showed reduced staining with alcian blue compared to Anabaena sp. PCC7120. We suggest that Zur is an important regulator of the enzymes involved in the synthesis and transport of the envelope polysaccharide layer, influencing heterocyst development and biofilm formation, both relevant processes for cell division and interaction with substrates in its ecological niche.

An active photosynthetic electron transfer chain required for mcyD transcription and microcystin synthesis in Microcystis aeruginosa PCC7806 - Emma Sevilla; Beatriz Martin-Luna; M. Teresa Bes; Maria F. Fillat; M. Luisa Peleato (Ecotoxicology, 2012)

Microcystin-LR synthesis as response to nitrogen: transcriptional analysis of the mcyD gene in Microcystis aeruginosa PCC7806 - Emma Sevilla; Beatriz Martin-Luna; Laura Vela; M. Teresa Bes; M. Luisa Peleato; Maria F. Fillat (Ecotoxicology, 2010)

Iron availability affects mcyD expression and microcystin‐LR synthesis in Microcystis aeruginosa PCC7806 - Emma Sevilla; Beatriz Martin‐Luna; Laura Vela; M. Teresa Bes; Maria F. Fillat; M. Luisa Peleato (Environmental Microbiology, 2008)
Summary Microcystins are toxins produced by cyanobacteria that entail serious health and environmental problems. They are cyclic heptapeptides synthesized via a mixed polyketide synthase/non‐ribosomal peptide synthetase system called microcystin synthetase. Environmental and nutritional factors that trigger microcystin synthesis are still debated and this work deals with the study of the influence of iron nutritional status on the microcystin synthesis. The results indicate that iron deficiency could be one of the inducing factors of the microcystin synthesis. For the first time, increased transcription of an essential mcy gene and correlative microcystin synthesis has been established. Real‐time PCR analysis of mcyD , and microcystin‐LR synthesis were studied on Microcystis aeruginosa PCC7806 grown in iron‐replete and iron‐deplete media. Iron starvation causes an increase of mcyD transcription, correlative to the increase of microcystin‐LR levels. Four transcription start points were identified for mcyD and two for mcyA , and they are not changed as a consequence of iron deficiency.

Effects of lindane on the photosynthetic apparatus of the cyanobacteriumanabaena - Marta Bueno; Maria F. Fillat; Reto J. Strasser; Ronald Maldonado-Rodriguez; Nerea Marina; Henry Smienk; Carlos Gómez-Moreno; Francisco Barja (Environmental Science and Pollution Research, 2004)

Monitoring Heterocyst Isolation in Anabaena PCC 7119 - Pedro Razquin; M. Teresa Bes; M. Luisa Peleato; Maria F. Fillat (Journal of Plant Biochemistry and Biotechnology, 2002)

Flavodoxin from the nitrogen-fixing cyanobacterium Anabaena PCC 7119 - Maria F. Fillat; Gerhard Sandmann; Carlos Gomez-Moreno (Archives of Microbiology, 1988)